Estudo sobre a expressão da metaloproteinase de matriz 7(MMP-7), a infecção pelos vírus HPV e EBV e o grau de malignidade de lesões do colo uterino - Silva, Naiara Soares Melo da (2016)
Cervical cancer is the second largest cause of deaths from malignant cancer among women worldwide. Many studies show the importance of the HPV virus in the onset of cervical cancer, but because of the monoclonal nature of this cancer, it is suspected that HPV infection may not be considered the only causal factor responsible for the development of cervical carcinoma. Studies have indicated that EBV may have a role in cooperation with the HPV16 tumor development. Such cooperation could influence the tumor microenvironment by creating a favorable niche for its progression. Cancer cells secrete enzymes that degrade the extracellular matrix (ECM). Such enzymes such as matrix metalloproteinases (MMPs) facilitate cell movement in tissues and induce the activity of growth factors that promote angiogenesis. Among the group of MMPs, MMP-7 seems to have a crucial role in the development of carcinogenesis, since its action has been associated with the cleavage and release of adhesion molecules important. In this sense, this study was performed to establish the relationship between the HPV coinfection / EBV and expression of MMP-7. They were examined immunohistochemically histological slides of cervical lesions biopsies of 60 patients aged 35 to 65 years. The samples were divided into high grade lesion and low grade and evaluated semiquantitatively by scoring system ranging from 0 to +++. Histopathological indexes the degree of injury were established. It observed a statistically significant association between high-grade lesion, the expression of MMP-7 and the presence of the HPV virus, with p = 0.007 at the junction portion squamocolumnar and p = 0.023 in the portion of the ectocervix. This correlation